(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper investigates image data compression as it is applicable to different fields of image processing, in order to reduce the volume of pictorial data which one may need to store or transmit, The research modifies a method for image data compression based on the two component code, in this coding technique, the image is partitioned into regions of slowly varying intensity. The contours separating the regions are coded by hadamard transform, while the rest image regions are coded by (AMBTC).